A stakeholder perspective on poverty reduction through the implementation of social marketing in the context of tourism - Türkmendağ, Tuba; Hassan, Azize (Frontiers in Psychology, 2024)
This study aims to establish a model that identifies the role of tourism, target group, tourism stakeholders, and the marketing mix factors in the context of tourism marketing based on behavior change and exchange theory, to contribute to poverty reduction through the implementation of social marketing in the tourism context. Phenomenology and grounded theory designs were used in the research. The research findings have revealed that social marketing tools and techniques are effective methods for reducing poverty in the context of tourism and have contributed to a better understanding of the impact of tourism on poverty in terms of roles, barriers, and expectations. It was concluded that for social marketing to be successfully applied in tourism, it needs to be adapted to government policies, institutions, and the private sector. According to the results of the study, government policies should be conducive to promoting behavior change through tourism. In line with the philosophy of social marketing, it is expected that the results will focus on behavior change in the target group in the context of tourism, creating shared values for society, and developing roles for the benefit of individuals and society.